Evaluación de esquemas de protección integral en redes de distribución radial de media tensión con generación distribuida - Jiménez Gutiérrez, Ricardo Arturo (Universidad de La Salle. Facultad de Ingeniería. Ingeniería Eléctrica., 2016)
The following document presents the development of the "Assessment of schemes of integrity protection systems in radial distribution networks of medium voltage with distributed generation", which was performed on the IEEE 13 bus test system, radial topology, adding distributed generation. Significantly for distributed and in order to model generation reverse flows, a synchronous machine at the node N684 it is implemented. To this work, the steady state voltage and current magnitudes was confirmed from a load flow, resulting values quite close to those set by the IEEE. Given this, it´s continued to put in failure each node in order to recognize the short circuit current, and already having the rated current of the same, it is possible to dimension each of the elements of protection were implemented. After having implemented each of the elements of protection, whether overcurrent relays or fuses, we proceeded to perform fault on the system, in order to recognize the response of them, as to each of the various failures such as balanced or unbalanced. Considering how each element of protection acts, their trip times, and the variation of the magnitudes of current when a node is in failure, it is possible to recognize the operation of the protection coordination, presenting proper clearance the failure and the selectivity with which they act the same. Besides having modern day conventional generators, it is also possible to find plants downstream system GD, located in distribution networks, specifically in centers of consumption, which leads to the network via reverse flows exist, the which could affect the operation of the system and continuity of electricity supply, since protection systems mostly are not dimensioned for such behavior.